Ammonia oxidation catalyst, preparation method and application thereof, and preparation method for preparing 2-cyanopyridine

By developing an ammonia oxidation catalyst containing V and Ti, the catalyst is distributed on the surface of TiO2 in a single-layer state, the problem of low yield of 2-methylpyridine to 2-cyanopyridine is solved, and an efficient and economical catalytic effect is achieved, with a 2-cyanopyridine yield reaching 92.8%.

CN119869572AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311395376.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

In the prior art, the yield of 2-methylpyridine is low in the product oxidation of 2-cyanopyridine, and the traditional kettle reaction has problems such as complicated operations and high pollution.

Method used

An ammonia oxidation catalyst including a support, an active component and an additive component is developed. The active component comprises V and Ti, and the additive component includes a non-metallic element, an alkali metal element and a Group VIB element. The catalyst is distributed on the surface of TiO2 in a single-layer state, and is prepared and calcined by spraying to improve activity and selectivity.

Benefits of technology

The yield of 2-cyanopyridine is significantly improved, both above 91%, up to 92.8%, and the ring opening and methyl shedding phenomenon during the reaction is reduced, and the economic and selectivity of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869572A_ABST
    Figure CN119869572A_ABST
Patent Text Reader

Abstract

The invention provides an ammoxidation catalyst, a preparation method and application thereof, and a preparation method for preparing 2-cyanopyridine, the catalyst comprises a carrier, an active component and an auxiliary agent component, the active component elements comprise V and Ti; the auxiliary agent component elements comprise one or more of non-metallic elements, alkali metal elements and VIB group elements; only a diffraction peak of a TiO2 crystal phase exists in an XRD (X-Ray Diffraction) pattern of the catalyst, and other active components and auxiliary components are distributed on the surface of TiO2 in a monomolecular layer state. The method has the advantages that the method is simple and convenient to operate, the method is particularly suitable for ammoxidation reaction, the yield of 2-cyanopyridine is 91% or above when the method is particularly applied to ammoxidation preparation of 2-cyanopyridine, the highest yield can reach 92.8%, and an excellent technical effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ammonia oxidation catalyst, a preparation method and application thereof, and a preparation method for 2-cyanopyridine. Background Art

[0002] Nitrogen heterocyclic and benzene ring cyano compounds are widely used in the fields of medicine, pesticides, food, etc. For example, 3-cyanopyridine is a raw material for the preparation of nicotinic acid and nicotinamide, both of which are essential components of B vitamins in organisms; aromatic nitriles are important intermediates in the pesticide and flame retardant industries. The traditional industrial production method of nitrile compounds is a kettle reaction, which is simple, convenient, and highly flexible, suitable for small-scale production, but also has problems such as low product yield, low purity, high wastewater generation, high energy consumption, poor working environment, and high labor intensity. Therefore, it is urgent to seek a green, efficient, environmentally friendly and more economical reaction process.

[0003] At present, Guangzhou Nansha Longsha Co., Ltd., Zhejiang Brothers Technology Co., Ltd., Hebei Yanuo Biochemical Co., Ltd., Anhui Hongyang Biochemical Co., Ltd., and Shandong Hongda Biotechnology Co., Ltd. have all achieved the industrialization of preparing 3-cyanopyridine by 3-methylpyridine gas phase ammoxidation method, and have achieved good economic returns. 2-methylpyridine is different from 3-methylpyridine. The methyl group in 2-methylpyridine is closer to the electron-withdrawing nitrogen atom. The methyl oxidation intermediate product during the ammoxidation process is very unstable, so the yield of 2-methylpyridine ammoxidation to 2-cyanopyridine is generally not high. At present, the synthesis methods of 2-cyanopyridine include kettle reaction and ammoxidation. The kettle reaction production operation is complicated, the molecular utilization is not high, and the pollution is large, which is not suitable for green environmental protection requirements. The ammoxidation method is simple, efficient, has high atomic utilization, produces less "three wastes", and the product yield can be greatly improved by selecting a suitable catalyst. At present, according to literature reports, the highest technical yield of 2-methylpyridine ammoxidation reaction is 85.6%, but it is understood that the yield in actual domestic industrial production is only about 72%. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of low product yield in the prior art and to provide an ammonia oxidation catalyst and a preparation method thereof, wherein the catalyst has the advantages of good economy, good product selectivity, high yield of target product, etc.

[0005] The present invention believes that since the methyl group in the 2-methylpyridine molecule is close to the nitrogen atom and is more active, the requirements for the catalyst in this reaction are more stringent than those in the ammoxidation of 3-methylpyridine. Therefore, an ammoxidation catalyst with moderate activity and high nitrilation ability is developed, which can effectively reduce the phenomenon of ring opening and methyl shedding during the reaction, reduce the generation of carbon dioxide and pyridine, and thus improve the yield of 2-cyanopyridine.

[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an ammonia oxidation catalyst, which includes a carrier, an active component and an auxiliary component, wherein the active component elements include V and Ti; the auxiliary component elements include non-metallic elements, alkali metal elements and one or more of Group VIB elements; only the diffraction peak of the TiO2 crystal phase exists in the XRD spectrum of the catalyst, and the other active components and auxiliary components are distributed on the TiO2 surface in the state of a monomolecular layer.

[0007] The second aspect of the present invention provides a method for preparing an ammonia oxidation catalyst, which comprises: preparing a vanadium source, a titanium source, an auxiliary component source, and optionally a polymer binder into a slurry to be sprayed, spraying the slurry to be sprayed onto a carrier by a spraying method, and then calcining.

[0008] A third aspect of the present invention provides use of an ammoxidation catalyst in preparing pyridine compounds by ammoxidation.

[0009] A fourth aspect of the present invention provides a method for preparing 2-cyanopyridine, the method comprising: contacting a raw material with a catalyst; the catalyst is the ammonia oxidation catalyst described in the present invention.

[0010] Through the above technical solution, the present invention has the following beneficial effects:

[0011] The ammonia oxidation catalyst of the present invention comprises a carrier, an active component and an auxiliary component, wherein the active component elements comprise V and Ti; the auxiliary component elements comprise one or more of non-metallic elements, alkali metal elements and VIB group elements; only the diffraction peak of the TiO2 crystal phase exists in the XRD spectrum of the catalyst, and the other active components and auxiliary components are distributed on the TiO2 surface in the state of a monomolecular layer, and are particularly suitable for ammonia oxidation reaction, especially when used for preparing 2-cyanopyridine by ammonia oxidation, the yield of 2-cyanopyridine is above 91%, and can reach up to 92.8%, thereby achieving excellent technical effects.

[0012] According to a preferred embodiment of the present invention, the catalyst of the present invention is prepared by a spraying method, and it is unexpectedly found that the activity, selectivity and mechanical stability of the catalyst obtained by controlling the calcination time are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 1 is the XRD diagram of the catalyst prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The present invention provides an ammonia oxidation catalyst, which comprises a carrier, an active component and an auxiliary component, wherein the active component elements comprise V and Ti; the auxiliary component elements comprise one or more of non-metallic elements, alkali metal elements and Group VIB elements; only the diffraction peak of the TiO2 crystal phase exists in the XRD spectrum of the catalyst, and the other active components and auxiliary components are distributed on the TiO2 surface in a monomolecular layer state.

[0016] According to a preferred embodiment of the present invention, the TiO2 crystal phase includes rutile TiO2 and / or anatase TiO2, preferably anatase TiO2≥90wt%. The above preferred embodiment can improve the activity of the catalyst.

[0017] In the present invention, the carrier can be a conventional choice in the art. According to a preferred embodiment of the present invention, the carrier is selected from at least one of alumina, silica and a ceramic ring. In the present invention, the ceramic ring is used as an example in the embodiment, but the present invention is not limited to this scope. The aforementioned preferred embodiment can reduce the production cost while ensuring the performance of the catalyst.

[0018] According to a preferred embodiment of the present invention, the additive component elements include at least two of non-metallic elements, alkali metal elements and Group VIB elements; preferably, the additive component elements include non-metallic elements, alkali metal elements and Group VIB elements at the same time. The above preferred embodiment can enhance the surface acidity of the catalyst and thus improve the selectivity of the product.

[0019] In the present invention, the non-metallic element in the auxiliary agent component can be a conventional choice in the art. According to a preferred embodiment of the present invention, the non-metallic element is selected from at least one of phosphorus, boron, selenium and arsenic. The aforementioned preferred embodiment can increase the acid center position on the catalyst surface and improve the selectivity of the catalyst.

[0020] In the present invention, the alkali metal element in the auxiliary agent component can be a conventional choice in the art. According to a preferred embodiment of the present invention, the alkali metal element is selected from at least one of lithium, sodium, potassium and rubidium. By adopting the above preferred embodiment, the acid strength of the catalyst surface can be optimized and the catalytic performance of the catalyst can be improved.

[0021] In the present invention, the VIB group element in the auxiliary agent component can be a conventional choice in the art. According to a preferred embodiment of the present invention, the VIB group element is selected from at least one of chromium, molybdenum and tungsten, but the present invention is not limited to this scope. The aforementioned preferred embodiment can increase the lattice oxygen defects on the catalyst surface and improve the oxidation activity of the catalyst.

[0022] In the present invention, the molar ratio of vanadium to titanium can be a conventional choice in the art. According to a preferred embodiment of the present invention, the molar ratio of vanadium to titanium is 1:24-32. The above preferred embodiment can improve the dispersion of vanadium on the surface of titanium dioxide, which is conducive to the formation of a monolayer.

[0023] In the present invention, the molar ratio of vanadium to the auxiliary agent component element can be a conventional choice in the art. According to a preferred embodiment of the present invention, the molar ratio of vanadium to the auxiliary agent component element is 1:0.1-1.5.

[0024] In the present invention, the molar ratio of vanadium to non-metallic elements can be selected in a wide range. According to a preferred embodiment of the present invention, the molar ratio of vanadium to non-metallic elements is 1:0.1-0.5. The above preferred embodiment can improve the selectivity of the catalyst.

[0025] In the present invention, the molar ratio of vanadium to alkali metal elements can be selected in a wide range. According to a preferred embodiment of the present invention, the molar ratio of vanadium to alkali metal elements is 1: 0.05-0.15. The above preferred embodiment can improve the selectivity of the catalyst.

[0026] In the present invention, the molar ratio of vanadium to the VIB group element can be selected in a wide range. According to a preferred embodiment of the present invention, the molar ratio of vanadium to the VIB group element is 1:0.15-0.4. The above preferred embodiment can improve the selectivity of the catalyst.

[0027] All ammonia oxidation catalysts having the aforementioned characteristics can be used in the present invention, and there is no special requirement for their preparation methods.

[0028] According to a preferred embodiment of the present invention, the method for preparing an ammonia oxidation catalyst comprises: preparing a slurry to be sprayed of an active component source and an auxiliary component source and preparing the slurry by a spraying method.

[0029] According to a preferred embodiment of the present invention, the solid content of the slurry to be sprayed is 25-40wt%.

[0030] By adopting the above-mentioned preferred embodiments, the catalytic performance of the catalyst can be improved.

[0031] According to a preferred embodiment of the present invention, the calcination time of the spray coating method is 10-18 hours, preferably 14-16 hours.

[0032] According to a preferred embodiment of the present invention, the slurry to be sprayed contains a polymer binder, and preferably the mass ratio of the polymer binder to the vanadium element is (0.05-0.2):1.

[0033] According to a preferred embodiment of the present invention, the polymer binder is selected from at least one of polyvinyl alcohol, polyvinyl pyrrolidone and polyacrylamide, preferably polyvinyl alcohol with a molecular weight of 25,000-150,000. In the present invention, 1795 type polyethylene glycol is used as an example in the examples, but the present invention is not limited to this scope.

[0034] By adopting the above-mentioned preferred embodiments, the reaction performance of the catalyst can be improved.

[0035] The invention provides a method for preparing an ammonia oxidation catalyst, which comprises: preparing a vanadium source, a titanium source, an auxiliary component source and optionally a polymer binder into a slurry to be sprayed, spraying the slurry to be sprayed onto a carrier by a spraying method, and then calcining.

[0036] In the present invention, there is no special requirement for the mass ratio of the polymer binder to the vanadium element. According to a preferred embodiment of the present invention, the mass ratio of the polymer binder to the vanadium element is (0.05-0.2) : 1. The above preferred embodiment can improve the firmness of the active component on the surface of the ceramic ring.

[0037] In the present invention, the polymer binder can be a conventional choice in the art. According to a preferred embodiment of the present invention, the polymer binder is selected from at least one of polyvinyl alcohol, polyvinyl pyrrolidone and polyacrylamide, preferably polyvinyl alcohol with a molecular weight of 25000-150000. In the present invention, 1795 type polyethylene glycol is used as an example in the embodiment, but the present invention is not limited to this scope. The above preferred embodiment can improve the reaction performance of the catalyst.

[0038] In the present invention, the molar ratio of the organic acid to the vanadium element in the spraying liquid can be a conventional choice in the art. According to a preferred embodiment of the present invention, the molar ratio of the organic acid to the vanadium element is (3-5) : 1. The above preferred embodiment can improve the selectivity of the catalyst.

[0039] In the present invention, the organic acid can be a conventional choice in the art. According to a preferred embodiment of the present invention, the organic acid is selected from at least one of citric acid, malic acid and oxalic acid. The above preferred embodiment can improve the selectivity of the catalyst.

[0040] According to a preferred embodiment of the present invention, the preparation method of the ammonia oxidation catalyst specifically comprises: (1) first mixing a vanadium source and an organic acid in a solvent to form a mixed solution A; (2) second mixing the mixed solution A and an additive source to form a mixed solution B; (3) third mixing the titanium source and the mixed solution B to form a mixed solution C; (4) fourth mixing the polymer binder and the mixed solution C to form a mixed solution D as the slurry to be sprayed, spraying the mixed solution D onto a carrier, and calcining. The above preferred embodiment can improve the catalytic performance of the catalyst.

[0041] In the present invention, there is no special requirement for the calcination conditions in step (4).

[0042] According to a preferred embodiment of the present invention, the calcination time is 10-18 hours, preferably 14-16 hours. The above preferred calcination time is adopted so that the active components are evenly dispersed on the surface of titanium dioxide, thereby forming a monomolecular layer.

[0043] According to a preferred embodiment of the present invention, the calcination temperature is 400-600°C, preferably 450-550°C.

[0044] By adopting the above-mentioned preferred embodiments, the catalytic performance of the catalyst can be improved.

[0045] In the present invention, there are no special requirements for the conditions of the third mixing and the fourth mixing.

[0046] In the present invention, there is no special requirement for the vanadium source, titanium source and auxiliary component source. The following is an exemplary description, but the scope of the present invention is not limited thereby. For example, the vanadium source is vanadium pentoxide; the titanium source is titanium dioxide; and the auxiliary component source is phosphoric acid, potassium nitrate and ammonium molybdate.

[0047] According to a preferred embodiment of the present invention, the temperature of the third mixing and the fourth mixing is 80-90°C.

[0048] According to a preferred embodiment of the present invention, there is no special requirement for the time of the third mixing, the purpose is to achieve uniform mixing, for example, the mixing time can be 8h, 10h, 12h, etc., and those skilled in the art can adjust it according to actual operation.

[0049] According to a preferred embodiment of the present invention, the fourth mixing time is 12h-24h, preferably 15h-20h.

[0050] According to a preferred embodiment of the present invention, the rotation speed of the third mixing and the fourth mixing is 150-200 rpm.

[0051] By adopting the above-mentioned preferred embodiments, the selectivity of the catalyst can be improved.

[0052] In the present invention, there are no special requirements for the conditions of the first mixing and the second mixing, and the purpose is to mix uniformly, for example, it can usually be achieved by slow dripping, heating, stirring, etc. The following is an exemplary description, but it does not limit the scope of the present invention.

[0053] According to a preferred embodiment of the present invention, the temperature of the first mixing and the second mixing is 70-85°C.

[0054] According to a preferred embodiment of the present invention, the time for the first mixing and the second mixing is 12-24 hours, preferably 15-20 hours.

[0055] According to a preferred embodiment of the present invention, the rotation speed of the first mixing and the second mixing is 150-200 rpm.

[0056] By adopting the above-mentioned preferred embodiments, the selectivity of the catalyst can be improved.

[0057] According to a preferred embodiment of the present invention, the molar ratio of the organic acid to the vanadium element is (3-5):1; preferably, the organic acid is selected from at least one of citric acid, malic acid and oxalic acid.

[0058] By adopting the above-mentioned preferred embodiment, the selectivity of the catalyst can be improved.

[0059] In the present invention, there is no special requirement for the spraying conditions. According to a preferred embodiment of the present invention, the spraying temperature is 80-180° C., preferably 100-160° C. The above preferred embodiment can improve the reaction performance of the catalyst.

[0060] There is no special requirement for the solvent in the present invention, as long as the purpose of dissolution can be achieved, and the prior art can be referred to. In the embodiments of the present invention, the solvent is illustrated by deionized water, but it is not limited to the scope of the present invention, and the amount of deionized water is not limited, and can be adjusted according to actual operation, as long as the solid content of the slurry to be sprayed is 25-40wt%.

[0061] The ammoxidation catalyst provided by the present invention has the advantages of good product selectivity, high yield, good economy and the like, and can be applied to various ammoxidation reactions for preparing pyridine compounds.

[0062] According to a preferred embodiment of the present invention, a method for preparing 2-cyanopyridine is provided, the method comprising: contacting a raw material with a catalyst; the catalyst is the ammonia oxidation catalyst of the present invention.

[0063] According to a preferred embodiment of the present invention, the contacting is carried out in a fixed bed reactor.

[0064] According to a preferred embodiment of the present invention, the raw materials include 2-methylpyridine, ammonia and air, and preferably the molar ratio of 2-methylpyridine, ammonia and air is 1:(1-10):(1-40).

[0065] By adopting the above-mentioned preferred embodiments, the product yield can be improved.

[0066] In the present invention, there is no special requirement for the contact conditions.

[0067] According to a preferred embodiment of the present invention, the contact temperature is 280-400°C.

[0068] According to a preferred embodiment of the present invention, the contact time is 8-20 hours.

[0069] According to a preferred embodiment of the present invention, the contact pressure is 101-120 kPa.

[0070] By adopting the above-mentioned preferred embodiments, the product yield can be improved.

[0071] In the present invention, the crystal structure of the catalyst is determined by X-ray diffraction spectrum (XRD), using a D8 X-ray powder diffraction (XRD) instrument from Bruker, Germany, using a Cu-Kα ray source, Kα1 wavelength λ = 1.5405980 angstroms Nickel filter, working voltage 40kV, current 40mA, scanning range 2θ=5-80°.

[0072] In the present invention, unless otherwise specified, percentages and contents are all based on mass. In the examples and comparative examples of the present invention, the titanium dioxide used is anatase.

[0073] The yield of 2-cyanopyridine is calculated according to the following formula:

[0074]

[0075] The stirring speed in the following examples was carried out at 200 rpm; the polyethylene glycol was 1795 type polyethylene glycol.

[0076] In the present invention, the solid content of the slurry to be sprayed is: the mass of the stable oxide after the active component is roasted / the total weight of the slurry*100%

[0077] Example 1

[0078] Weigh 15g oxalic acid and 300mL distilled water in a flask, stir and heat to 85°C, and after the oxalic acid is completely dissolved, prepare an oxalic acid solution. Add 5g vanadium pentoxide to the prepared oxalic acid solution and continue stirring to obtain a vanadium oxalate solution. Add 1.2g phosphoric acid, 0.6g potassium nitrate, and 3g ammonium molybdate to the solution (maintaining the temperature at 85°C). Add 100g titanium dioxide (90wt% of anatase TiO2 and the rest of rutile) to the solution, continue heating and stirring until uniform, and the stirring temperature is 85°C. Dissolve 0.5g polyvinyl alcohol in 10ml water, add it to the catalyst precursor slurry (solid content: 35%), and continue heating and stirring for 18h.

[0079] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 120℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace, bake it at 450℃ for 15h, and get the catalyst after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monolayer.

[0080] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 92.8%.

[0081] Figure 1 The XRD patterns of the catalysts prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 1 It is shown that according to the catalyst prepared in Example 1, the active components are uniformly dispersed on the TiO2 surface in the form of a monomolecular layer.

[0082] Example 2

[0083] Weigh 15g oxalic acid and 300mL distilled water in a flask, stir and heat to 85°C, and after the oxalic acid is completely dissolved, prepare an oxalic acid solution. Add 5g vanadium pentoxide to the prepared oxalic acid solution and continue stirring to obtain a vanadium oxalate solution. Add 1.6g phosphoric acid, 0.3g potassium nitrate, and 1.8g ammonium molybdate to the solution (maintaining the temperature at 85°C). Add 100g titanium dioxide (90wt% of anatase TiO2 and the rest of rutile) to the solution, continue heating and stirring until uniform, and the stirring temperature is 85°C. Dissolve 0.5g polyvinyl alcohol in 10ml water, add it to the catalyst precursor slurry (solid content: 34%), and continue heating and stirring for 18h.

[0084] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 140℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace and bake it at 550℃ for 14 hours. After natural cooling, the catalyst is obtained. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monomolecular layer.

[0085] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 92.1%.

[0086] Example 3

[0087] Weigh 15g oxalic acid and 300mL distilled water in a flask, stir and heat to 85°C, and after the oxalic acid is completely dissolved, prepare an oxalic acid solution. Add 5g vanadium pentoxide to the prepared oxalic acid solution and continue stirring to obtain a vanadium oxalate solution. Add 3g phosphoric acid, 0.9g potassium nitrate, and 4.8g ammonium molybdate to the solution (maintaining the temperature at 85°C). Add 100g titanium dioxide (90wt% of anatase TiO2) to the solution, continue heating and stirring until uniform, and the stirring temperature is 85°C. Dissolve 0.5g polyvinyl alcohol in 10ml water, add it to the catalyst precursor slurry (solid content: 34%), and continue heating and stirring for 18h.

[0088] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 170℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace, bake it at 500℃ for 16 hours, and get the catalyst after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monomolecular layer.

[0089] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 92.3%.

[0090] Example 4

[0091] All are the same as Example 1, except that the titanium dioxide used is 60wt% of anatase TiO2 (the rest is rutile). Under the same evaluation conditions, the evaluation results show that the yield of 2-cyanopyridine is 82.4%.

[0092] Example 5

[0093] All conditions were the same as in Example 1, except that 2 g of vanadium pentoxide was added.

[0094] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 120℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace, bake it at 450℃ for 15h, and get the catalyst after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monolayer.

[0095] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 87.6%.

[0096] Example 6

[0097] All conditions were the same as in Example 1, except that the phosphoric acid feed was 0.3 g.

[0098] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 120℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace, bake it at 450℃ for 15h, and get the catalyst after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monolayer.

[0099] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 90.3%.

[0100] Example 7

[0101] All conditions were the same as in Example 1, except that the potassium nitrate feed was 0.15 g.

[0102] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 120℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace, bake it at 450℃ for 15h, and get the catalyst after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monolayer.

[0103] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 90.5%.

[0104] Example 8

[0105] All conditions are the same as in Example 1, except that the amount of ammonium molybdate added is 6 g.

[0106] Take 1 portion of the precursor slurry and put it into the sprayer. The spraying temperature is 120℃, and it is evenly sprayed on the ceramic ring carrier. Place it in a muffle furnace, bake it at 450℃ for 15h, and get the catalyst after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monolayer.

[0107] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 89.9%.

[0108] Example 9

[0109] Weigh 15g oxalic acid and 200mL distilled water in a flask, stir and heat to 85°C, and after the oxalic acid is completely dissolved, prepare an oxalic acid solution. Add 5g vanadium pentoxide to the prepared oxalic acid solution and continue stirring to obtain a vanadium oxalate solution. Add 1.2g phosphoric acid, 0.6g potassium nitrate, and 3g ammonium molybdate to the solution (maintaining the temperature at 85°C). Add 100g titanium dioxide to the solution, continue heating and stirring until uniform, and the stirring temperature is 85°C. Dissolve 0.5g polyvinyl alcohol in 10ml water, add it to the catalyst precursor slurry (solid content: 54%), and continue heating and stirring for 18h.

[0110] Take 1 portion of the precursor slurry and put it into the sprayer, spray it evenly on the porcelain ring carrier at a spraying temperature of 120°C, place it in a muffle furnace, bake it at 450°C for 15h, and obtain the catalyst after natural cooling.

[0111] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 88.5%.

[0112] Example 10

[0113] All conditions were the same as in Example 1, except that the amount of polyvinyl alcohol added was 0.05 g.

[0114] Take 1 portion of the precursor slurry and put it into the sprayer, spray it evenly on the porcelain ring carrier at a spraying temperature of 120°C, place it in a muffle furnace, bake it at 450°C for 15h, and obtain the catalyst after natural cooling.

[0115] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 89.6%.

[0116] Embodiment 11

[0117] All conditions are the same as in Example 1, except that: 1 portion of the precursor slurry is loaded into a sprayer, the spraying temperature is 120°C, and it is evenly sprayed on the ceramic ring carrier, placed in a muffle furnace, calcined at 450°C for 11 hours, and cooled naturally to obtain a catalyst.

[0118] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 90.2%.

[0119] Example 12

[0120] Weigh 15g oxalic acid and 300mL distilled water in a flask, stir and heat to 85°C, and after the oxalic acid is completely dissolved, prepare an oxalic acid solution. Add 5g vanadium pentoxide to the prepared oxalic acid solution and continue stirring to obtain a vanadium oxalate solution. Add 1.2g phosphoric acid, 0.6g potassium nitrate, and 3g ammonium molybdate to the solution (maintaining the temperature at 85°C). Add 100g titanium dioxide to the solution, continue heating and stirring until uniform, and the stirring temperature is 85°C. Dissolve 0.5g polyvinyl alcohol in 10ml water, add it to the catalyst precursor slurry (solid content: 35%), and continue heating and stirring for 13h.

[0121] Take 1 portion of the precursor slurry and put it into the sprayer, spray it evenly on the porcelain ring carrier at a spraying temperature of 120°C, place it in a muffle furnace, bake it at 450°C for 15h, and obtain the catalyst after natural cooling.

[0122] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 90.1%.

[0123] Embodiment 13

[0124] All conditions are the same as those in Example 1, except that: 1 portion of the precursor slurry is loaded into a sprayer, the spraying temperature is 85°C, and it is evenly sprayed on the ceramic ring carrier. It is placed in a muffle furnace and calcined at 450°C for 15 hours, and the catalyst is obtained after natural cooling. The XRD spectrum of the catalyst only has the diffraction peak of the TiO2 crystal phase, and the other components are distributed on the TiO2 surface in the state of a monomolecular layer.

[0125] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 91.2%.

[0126] Embodiment 14

[0127] All are the same as Example 1. 15 g of oxalic acid, 5 g of vanadium pentoxide, 1.2 g of phosphoric acid, 0.6 g of potassium nitrate, 3 g of ammonium molybdate and 100 g of titanium dioxide (90 wt % of anatase TiO2 and the rest of rutile) and 300 mL of distilled water are weighed into a flask (temperature 85°C) to form a catalyst precursor slurry. Then, 0.5 g of polyvinyl alcohol is dissolved in 10 ml of water and added to the catalyst precursor slurry (solid content: 35%). Heating and stirring are continued for 18 h.

[0128] Take 1 portion of the precursor slurry and put it into the sprayer, spray it evenly on the porcelain ring carrier at a spraying temperature of 120°C, place it in a muffle furnace, bake it at 450°C for 15h, and obtain the catalyst after natural cooling.

[0129] Under the same evaluation conditions as in Example 1, the evaluation results showed that the yield of 2-cyanopyridine was 89.8%.

[0130] Comparative Example 1

[0131] All conditions are the same as in Example 1, except that: 1 portion of the precursor slurry is loaded into a sprayer, the spraying temperature is 120°C, and it is evenly sprayed on the ceramic ring carrier, placed in a muffle furnace, calcined at 450°C for 5 hours, and cooled naturally to obtain a catalyst.

[0132] The catalyst particles are 25 mesh. The fixed bed reactor was 400 mm long, the catalyst loading was 4 g, the reaction system was at normal pressure, the reaction temperature was 365 °C, the raw material molar ratio was 2-picoline: NH3: air = 1:5:27, and the catalyst weight load (W2-picoline / Wcat) was 0.055 h -1 The results of the evaluation for 2h showed that the yield of 2-cyanopyridine was 60.8%.

[0133] Figure 1 The XRD spectrum of the catalyst prepared in Comparative Example 1 is given. Figure 1 It can be seen that even if the ratio of the active components is the same, but the calcination time is not within the range of the present invention, a crystalline phase other than TiO2 will appear in the XRD spectrum of the prepared catalyst.

[0134] It can be seen from the evaluation results that the catalyst prepared by the method of the present invention has significantly better reaction performance when used to catalyze the ammoxidation of 2-methylpyridine to prepare 2-cyanopyridine.

[0135] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An ammonia oxidation catalyst, characterized in that The catalyst comprises a carrier, an active component and an auxiliary component, wherein the active component elements include V and Ti; the auxiliary component elements include one or more of non-metallic elements, alkali metal elements and VIB group elements; The XRD spectrum of the catalyst only shows the diffraction peak of TiO2 crystal phase, and other active components and auxiliary components are distributed on the TiO2 surface in the form of a monomolecular layer.

2. The catalyst according to claim 1, wherein TiO2 crystalline phase comprises rutile TiO2 and / or anatase TiO2, preferably anatase TiO2≥90wt%; and / or The carrier is selected from at least one of alumina, silica and a ceramic ring; and / or The auxiliary agent component elements include at least two of non-metallic elements, alkali metal elements and Group VIB elements; Preferably, the auxiliary agent component elements include non-metallic elements, alkali metal elements and Group VIB elements at the same time; and / or The non-metallic element is at least one selected from phosphorus, boron, selenium and arsenic; and / or The alkali metal element is at least one selected from lithium, sodium, potassium and rubidium; and / or The VIB group element is at least one element selected from chromium, molybdenum and tungsten.

3. The catalyst according to claim 1 or 2, wherein The molar ratio of vanadium to titanium is 1:24-32; and / or The molar ratio of vanadium to the additive component element is 1:0.1-1.5; Preferably, The molar ratio of vanadium to non-metallic elements is 1:0.1-0.5; and / or The molar ratio of vanadium to alkali metal element is 1:0.05-0.2; and / or The molar ratio of vanadium to VIB group elements is 1:0.15-0.5; and / or The preparation method of the ammonia oxidation catalyst comprises: preparing a slurry to be sprayed of an active component source and an auxiliary component source and preparing the slurry by a spraying method, preferably; The solid content of the slurry to be sprayed is 25-40wt%; The calcination time for the spraying method is 10-18h, preferably 14-16h; Preferably, the slurry to be sprayed contains a polymer binder, and preferably, the mass ratio of the polymer binder to the vanadium element is (0.05-0.2):1; and / or The polymer binder is selected from at least one of polyvinyl alcohol, polyvinyl pyrrolidone and polyacrylamide, preferably polyvinyl alcohol with a molecular weight of 25,000-150,000.

4. A method for preparing the ammonia oxidation catalyst according to any one of claims 1 to 3, characterized in that: The method includes: A vanadium source, a titanium source, an auxiliary component source and an optional polymer binder are prepared into a slurry to be sprayed, and the slurry to be sprayed is sprayed onto a carrier by a spraying method, and then calcined. The calcination time is 10-18 hours.

5. The preparation method according to claim 4, wherein: The titanium source is titanium dioxide, wherein anatase TiO2 is ≥ 90wt%; The mass ratio of the polymer binder to the vanadium element is (0.05-0.2):1; and / or The polymer binder is selected from at least one of polyvinyl alcohol, polyvinyl pyrrolidone and polyacrylamide, preferably polyvinyl alcohol with a molecular weight of 25000-150000; and / or The slurry to be sprayed contains an organic acid; preferably, the molar ratio of the organic acid to the vanadium element is (3-5):1; Preferably, the organic acid is selected from at least one of citric acid, malic acid and oxalic acid; and / or The solid content of the slurry to be sprayed is 25-40wt%; and / or the solvent in the sprayed slurry includes deionized water; and / or The calcination time is 14-16 hours; and / or the calcination temperature is 400-600°C, preferably 450-550°C; and / or The spraying conditions include: The temperature is 80-180°C, preferably 100-160°C.

6. The preparation method according to claim 4 or 5, wherein: The method includes: (1) a vanadium source and an organic acid are first mixed in a solvent to form a mixed solution A; (2) performing a second mixing of the mixed solution A and the auxiliary agent source to form a mixed solution B; (3) performing a third mixing of the titanium source and the mixed solution B to form a mixed solution C; (4) The polymer binder is mixed with the mixed solution C for the fourth time to form a mixed solution D as the slurry to be sprayed, and the mixed solution D is sprayed onto the carrier and calcined.

7. The method according to any one of claims 4 to 6, wherein: The conditions of the third mixing and the fourth mixing each include: The temperature is 80-90°C; and / or The fourth mixing time is 12h-24h, preferably 15h-20h; and / or The solvent is deionized water; and / or The conditions of the first mixing and the second mixing each include: The temperature is 70-85℃.

8. Application of ammonia oxidation catalyst in the preparation of pyridine compounds by ammonia oxidation.

9. A method for preparing 2-cyanopyridine, characterized in that: The method comprises: contacting a feedstock with a catalyst; The catalyst comprises the ammonia oxidation catalyst according to any one of claims 1 to 3.

10. The method according to claim 9, wherein: The contacting is carried out in a fixed bed reactor; and / or The raw materials include 2-methylpyridine, ammonia and air, and preferably the molar ratio of 2-methylpyridine, ammonia and air is 1:(1-10):(1-40); and / or The contact conditions include: Temperature 280-400°C; and / or Time 8-20h; and / or Pressure 101-120kPa.

Citation Information

Patent Citations

  • Catalyst for producing 3-cyano pyridine as well as preparation method and use thereof

    CN101433836A

  • Vanadium catalyst and preparation method thereof

    CN111097464A

  • Alkyl pyridine ammoxidation catalyst and preparation method thereof

    CN111097468A

  • Catalyst for synthesizing pyromellitic dianhydride as well as preparation method and application of catalyst

    CN114643052A

  • Wear-resistant ammoxidation catalyst as well as preparation method and application thereof

    CN114950404A